Seismic Response Estimation of Multi-Story Structures Equipped with a Cost-Effective Earthquake Protection System - Enokida, Ryuta; Yenidogan, Cem (MDPI, 2025)
This study presents a new method for estimating the seismic responses of multi-story structures equipped with a cost-effective earthquake protection system. This system comprises a graphite lubrication interface, targeting a friction coefficient of approximately 0.2, and a feasible restoring force mechanism to suppress residual displacements. It utilizes the concept of sliding systems through conventional and affordable construction materials although it acts like a fixed-based structure until exceeding the threshold level. This multi-story estimation procedure is an extension of the recently developed procedure for estimating the shear coefficient of a single-story sliding structure with a restoring force mechanism. In the new estimation procedure, a multi-story superstructure is firstly regarded as a single-story superstructure to determine the shear coefficient. Then, the shear coefficient is distributed to each story through floor distribution coefficients considering the mass ratios. The contribution of ground motion intensity is also incorporated into the new form for improving accuracy. For this examination, incremental dynamic analyses (IDAs) are performed for three and six-story free-standing structures, both with and without a restoring force capability. The results clarify the reliability of the new estimation, which matched the IDA results within the +/- 20% error. The improvement in accuracy achieved by incorporating ground motion intensity is also clarified. The multi-story estimation with the improvement can reasonably estimate the seismic response of sliding structures, without dynamic analysis, solely based on structural properties. This greatly benefits the design process. Furthermore, the IDA results clarified the significant benefits of multi-story sliding structures employing graphite lubrication and properly designed restoring force mechanisms in reducing structural damage and suppressing residual sliding displacements.
Keywords: seismic response estimation; free-standing structure; graphite lubrication; restoring force mechanism; incremental dynamic analysis; BASE-ISOLATED STRUCTURES; ISOLATED BUILDINGS; RESTORING CAPABILITY; DYNAMIC-ANALYSIS; STEEL; DESIGN; ISOLATOR; BEHAVIOR; DISPLACEMENT; COEFFICIENT; Construction & Building Technology; Engineering